Emerging B and plasma cell-targeting immune therapies in idiopathic inflammatory myopathies - Groener, Marwin; Paik, Julie J. (Frontiers in Immunology, 2025)
Autoantibodies play a crucial role in the diagnosis and clinical characterization of idiopathic inflammatory myopathies (IIM). These antibodies are categorized into myositis-specific autoantibodies (MSAs), which are unique to IIM, and myositis-associated autoantibodies (MAAs), which can be seen with other autoimmune diseases. Both plasmablasts and plasma cells contribute to the production of these autoantibodies. Current B cell-targeted therapies, such as rituximab, have shown promise in refractory IIM, although their limitations – particularly in targeting plasmablasts and plasma cells – highlight the need for alternative agents with greater efficacy. This review discusses the evolving landscape of B cell and plasma cell-targeted immunotherapies in IIM, including next-generation anti-CD20 antibodies, BAFF inhibition, anti-CD19 CAR-T cells, BCMA-targeted therapies, and anti-CD38 antibodies. Most studies on the use of these novel treatment strategies in IIM have reported positive outcomes, although the number of patients treated is small. While these therapies represent a paradigm shift, further randomized clinical trials are needed to identify optimal strategies for IIM management and establish long-term safety and efficacy.